Safe Circumcision Anaesthesia A Review - Loban, Akhter Hossain; Islam, Md Shahidul (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Circumcision of Neonate, Infant, Children as well as adult is done for many purposes of them religious, disease process and to prevent some diseases. Pain is the main problem of circumcision. Infant and Children will not allow local analgesia. General anaesthesia needed for them. Neonate and adult may allow local anaesthesia. So, local anaesthesia, general anaesthesia, combination of local and general anaesthesia can be given. It is a minor procedure but anaesthesia for circumcision is not easy and should not be taken lightly. Complications related to circumcision anaesthesia can be minimized by proper selection of patient and type of anaesthesia. In our country circumcision done for religious purpose so a large number of circumcisions done by professional hazzam (non doctor). Doctors including general practitioners and surgeons are also doing this procedure. Complications related to anaesthesia are mainly laryngospasm and hypoxia and ultimately cardiac and cerebral complications. Some of them are highlighted in the media and newspapers but unknown cases are not less. If we can prevent and manage the complications like laryngospasm then this procedure can be done safely. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19817 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 52-53